Near Surface Atmospheric Temperatures at Jezero From Mars 2020 MEDA Measurements. Issue 3 (3rd March 2023) - Munguira, A.; Hueso, R.; Sánchez‐Lavega, A.; de la Torre‐Juarez, M.; Martínez, G. M.; Newman, C. E.; Sebastian, E.; Lepinette, A.; Vicente‐Retortillo, A.; Chide, B.; Lemmon, M. T.; Bertrand, T.; et al.
Abstract: The Mars Environmental Dynamics Analyzer instrument on Mars 2020 has five Atmospheric Temperature Sensors at two altitudes (0.84 and 1.45 m) plus a Thermal InfraRed Sensor that measures temperatures on the surface and at ∼40 m. We analyze the measurements from these sensors to describe the evolution of temperatures in Jezero up to mission sol 400 (solar longitude L S  = 13°–203°). The diurnal thermal cycle is characterized by a daytime convective period and a nocturnal stable atmosphere with a variable thermal inversion. We find a linear relationship between the daytime temperature fluctuations and the vertical thermal gradient with temperature fluctuations that peak at noon with typical values of 2.5 K at 1.45 m. In the late afternoon (∼17:00 Local True Solar Time), the atmosphere becomes vertically isothermal with vanishing fluctuations. We observe very small seasonal changes in air temperatures during the period analyzed. This is related to small changes in solar irradiation and dust opacity. However, we find significant changes in surface temperatures that are related to the variety of thermal inertias of the terrains explored along the traverse of Perseverance. These changes strongly influence the vertical thermal gradient, breaking the nighttime thermal inversion over terrains of high thermal inertia. We explore possible detections of atmospheric tides on near‐surface temperatures and we examine variations in temperatures over timescales of a few sols that could be indicative of atmospheric waves affecting near‐surface temperatures. We also discuss temperatures during a regional dust storm at L S  = 153°–156° that simultaneously warmed the near surface atmosphere while cooling the surface. Plain Language Summary: The Mars Environmental Dynamics Analyzer instrument on the Mars 2020 Perseverance rover records temperatures in Jezero at four altitudes from the surface to 40 m. We describe the evolution of temperatures over the first 400 Martian days of the mission from northern spring to early autumn. Diurnal temperatures show an unstable convective regime during the daytime and a stable atmosphere at night. Daytime convection produces thermal fluctuations that peak at noon with typical values of 2.5 K at 1.45 m. These thermal fluctuations vanish in the late afternoon when an isothermal atmosphere is observed from the surface up to 40 m. We also find a linear relationship between the daytime temperature fluctuations and the thermal gradient between the surface and the atmosphere. We find very little seasonal change in air temperatures. However, the thermal inertia of the terrain affects surface temperatures, and the nighttime thermal inversion breaks over terrains with high thermal inertia. We investigate the possible detection in near surface temperatures of thermal tides and atmospheric waves. Finally, we show the thermal response of the surface and the atmosphere during the passage of a regional dust storm with a simultaneous cooling of the surface and warming of the near‐surface atmosphere. Key Points: Surface and atmospheric temperatures at Jezero show small seasonal variations from Spring to early Autumn that agree with models The intensity of daytime convective fluctuations is correlated with vertical thermal gradients, which depend on the surface thermal inertia A dust storm significantly heated the lower atmosphere while cooling the surface indicating strong radiative effects of low altitude dust